Parkinson's disease biomarkers based on α‐synuclein. Issue 5 (28th July 2019) - Fayyad, Muneera; Salim, Safa; Majbour, Nour; Erskine, Daniel; Stoops, Erik; Mollenhauer, Brit; El‐Agnaf, Omar M. A.
Abstract: Parkinson's disease is the second most common neurodegenerative disorder after Alzheimer's disease and is estimated to affect approximately 1–4% of individuals aged over 60 years old. Although considerable efforts have been invested into developing disease‐modifying therapies for Parkinson's disease, such efforts have been confounded by the difficulty in accurately diagnosing Parkinson's disease during life to enable accurate patient stratification for clinical trialling of candidate therapeutics. Therefore, the search for effective biomarkers that can be accurately evaluated during life with non‐invasive means is a pressing issue in the field. Since the discovery of α‐synuclein (α‐syn) as a protein linked to a familial form of Parkinson's disease, later identified as the major protein component of the neuropathological hallmark of idiopathic Parkinson's disease, considerable interest has focused on this protein and its distinct conformers. We describe here the progress that has been made in the area of Parkinson's disease biomarker discovery with a focus on α‐synuclein. In particular, we highlight the novel assays that have been employed and the increasing complexity in evaluating α‐synuclein with regard to the considerable diversity of conformers that exist in the biofluids and peripheral tissues under disease conditions. "This article is part of the Special Issue Synuclein." Abstract : Parkinson's disease (PD) is characterized by a marked loss in the dopaminergic neurons of the substantia nigra, accompanied by an abnormal aggregation of the protein, α‐synuclein, into oligomers and later, insoluble fibrils. PD pathogenesis starts many years before motor symptoms manifest and a diagnosis is made, providing an opportunity for therapeutic interventions. To date, the major obstacle that impedes pre‐symptomatic diagnosis is the lack of biomarkers for objective early diagnosis. Herein, we describe the progress that has been made in the area of PD biomarker discovery with a focus on α‐synuclein conformers in biofluids and peripheral tissues under disease conditions. "This article is part of the Special Issue Synuclein."